THE ROLE OF PROJECT METHODS IN REVEALING CREATIVITY OF ENGLISH TEACHER - Usmonova, Dilnoza (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This research paper gives information about the basics of project methodology’s provisions, and various prospects of applying project methods in English language classes in universities, especially as one of the means of establishing cross-cultural competence. Nowadays, traditional methods and approaches are opposed to project activities, in the project method, the central figures are the students, only the teacher assists and he/she is a correspondent in the procedure. Project methods encourage learners to deal with real-life problems and improve the advancement of learner autonomy. The applicable establishment of project methods in the English classroom environment is available only via a complicated analysis of the curriculum of the training field, the material design of the educational content in consideration of the age, the foreign communicational skills, level of the learners, professional establishment of cognitive tasks of the learners while teaching and individual work, applying of ICT in the educational procedure.